MODEL KOMUNIKASI LITERASI DIGITAL DALAM MENGATASI UJARAN KEBENCIAN DI MEDIA SOSIAL - Andriani, Astri Dwi; Fitri, Susanti Ainul; Muchtar, Khoiruddin (Interaksi: Jurnal Ilmu Komunikasi, 2024)
The growth of social media users in Indonesia has increased online interactions, but has also triggered a surge in hate speech. Hate speech threatens social cohesion and can lead to violence. This article explores how digital literacy can be used as a tool to reduce the spread of hate speech on social media. This study uses a qualitative method with a literature study approach and in-depth interviews with digital literacy experts. The results show that good digital literacy can improve the ability of social media users to recognize and counter hate speech. The conclusion of this study is the importance of digital literacy education in the curriculum and educational programs targeting internet users. This scheme includes a multi-layered approach from upstream (prevention) to downstream (law enforcement), with the Ministry of Communication and Information playing a central role in cooperation with digital platforms, enforcing regulations, and community digital literacy to reduce the spread of hate speech in Indonesia.